2020
DOI: 10.3390/app10030993
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcination Temperature on Photocatalytic Activity of Synthesized TiO2 Nanoparticles via Wet Ball Milling Sol-Gel Method

Abstract: In this work, TiO2 nanoparticles were successfully synthesized with narrow size distribution via a wet ball milling sol-gel method. The effect of calcination temperature on photocatalytic activity was observed from particle size, crystallite size, and phase transition of TiO2 nanoparticles. Increasing calcination temperature increased particle size, crystallite size, and the crystallinity of synthesized TiO2. Phase transition depended on variation in calcination temperatures. A two-phase mixture of anatase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(46 citation statements)
references
References 45 publications
5
41
0
Order By: Relevance
“…These planes belong to tetragonal anatase phase of Cu-doped TiO 2 that correlates with standard spectrum (JCPDS card 21-1272) along with space group I4 1 /amd (141) with corresponding cell dimensions of a ¼ 3.758 A and c ¼ 9.513 A. [47][48][49][50][51][52][53][54][55][56][57] The lattice spacing is $0.35 nm for TiO 2 equivalent to (101) facet, also validated with HR-TEM observation (see Fig. 9).…”
Section: Resultsmentioning
confidence: 62%
“…These planes belong to tetragonal anatase phase of Cu-doped TiO 2 that correlates with standard spectrum (JCPDS card 21-1272) along with space group I4 1 /amd (141) with corresponding cell dimensions of a ¼ 3.758 A and c ¼ 9.513 A. [47][48][49][50][51][52][53][54][55][56][57] The lattice spacing is $0.35 nm for TiO 2 equivalent to (101) facet, also validated with HR-TEM observation (see Fig. 9).…”
Section: Resultsmentioning
confidence: 62%
“…The longer the ligand (-OR) in the precursor, the slower the hydrolysis rate. It is because of steric hindrance due to the longer R chain, therefore the transfer of ligand (-OR) with hydroxyl group (-OH) is slower [15].…”
Section: Results and Discussion Tio 2 Synthesismentioning
confidence: 99%
“…In condensation process, there was a change from sol to gel. The used 110 o C is to dried and evaporate the solvent leftover in the gel and gel that has cross linking addition in unreacted group of -OH and -OR, thus it can form good solids [15]. The anatase crystal phase was formed at a temperature of 400 °C and the growth of anatase crystals increased along with the increase in calcination temperature, at a temperature of 400-600 °C rutile nucleation occurred [6].…”
Section: Tio 2 Sio 2 Composite Synthesismentioning
confidence: 99%
“…The band gap of synthesized photocatalyst is 3.2 eV which is shown that the anatase phase is dramatically higher than the rutile phase. The anatase phase has the highest photocatalytic activity because of an indirect band gap of the anatase phase (Phromma et al 2020).…”
Section: Optimum Condition Of Ammonia Removalmentioning
confidence: 99%